Configuration of the active region for the Ge-on-Si photodetector based on carrier mobility - Chang, Chang; Xie, Xiaoping; Li, Tiantian; Cui, Jishi (Frontiers in Physics, 2023)
The design of vertical and lateral PIN Ge-on-Si photodetectors was motivated by the disparity in electron and hole mobilities. In the case of vertical PIN junction detectors, configuring the slab region as n-type doping leads to a notable increase in the bandwidth of approximately 20 GHz compared to utilizing p-type doping for the slab. For lateral PIN junction detectors, we determined that setting the length of the n-type slab region to be 2.8 times that of the p-type slab region, based on the carrier saturation drift rate ratio, does not compromise the bandwidth. This configuration enhances the bandwidth while minimizing light absorption loss from the electrode. The proposed design in this study enhances the performance of Ge-on-Si photodetectors without adding complexity to the fabrication process. The principles applied in this study serve as instructive references for the conceptualization of other photonic or electronic devices, reinforcing the widespread applicability of these design strategies.